Underage female athletes' motor abilities developing by aesthetic gymnastics toolkit - Bezhentseva, L. M. (Theory and Practice of Physical Culture, 2017)
Objective of the study was to rate benefits of a new aesthetic gymnastics toolkit applied to develop motor skills in underage female athletes. Experimental work under the study was performed at Olympia Aesthetic Gymnastics Club in Tomsk in the 2016-17 year. Subject to the study were 30 underage (5-6 years old) female beginner gymnasts split up into Study Group (n=15) and Reference Group (n=15). The RG was trained as required by the valid standard program and practical guidelines; and the SG was trained under a new aesthetic gymnastics based model (of our design) with a high priority given to special active games to facilitate the motor skills and physical abilities building process. The experimental aesthetic gymnastics based model was found beneficial for the underage athletes` motor skills development process.